If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3v = 0 Solving 9 + -3v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3v = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -3v = 0 + -9 -3v = 0 + -9 Combine like terms: 0 + -9 = -9 -3v = -9 Divide each side by '-3'. v = 3 Simplifying v = 3
| 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= | | -0.666+4w=-0.111 | | -7+4(1+5a)= | | 9xa+1=8a | | 2v^2(8v^2+6vb-5b^2)= | | (z^4/16)^3/4 | | (m-3)+5=16 | | 2(10x-3)-4x= | | x^2-8x+132=120 | | 5(7+6m)-10= | | 24(y-1)=-6(5+y) | | -4b+3(b+5)= | | -(v+3)-5= | | Yk+yq=k | | 4-sqrt8/sqrtx-6 | | (35x^2-32x)/(7x-5) | | 2r-(-3+6t)= | | 7x^2+5x-11=61-50x | | 3(x+3)+3=3x+7 | | 5(1-4n)-9n= | | -6m+3=4m-4 | | 5n+4(10n+6)= | | 2x-50=-10+10 | | 2x-4(10n+6)= |